Communication Behavior of Mandailing Culture Husband and Wife at Different Age Different Wedding in Sopoonggang Baru Village (Case Study of Wife Older Than Husband) (Pena Cendekia Insani, 2023)
This study explores the phenomenon of couples who marry at different ages with the aim of knowing how the communication behavior of husband and wife in the Mandailing culture in marriages with a large age difference in the Mandailing culture. There are many differences in marriage with a large age difference between husband and wife which tends to make it difficult for couples to unite thoughts, ideas and opinions. This will be a challenge for the household so that it can make a household that is sakinah, mawaddah, warahmah. This research uses a qualitative approach with a descriptive qualitative research type. Source of data obtained from primary and secondary data. Data collection techniques were used through observation, in-depth interviews and documentation with three husband and wife couples with a much older age difference than their husbands with a distance of five years, seven years and ten years. The results of research conducted in Sopoonggang Baru Hamlet show that different age marriages are much older for wives than husbands, but there are problems that often occur in domestic life, including: difficult to control emotions, relationships decreased sexual relations between husband and wife, jealousy, differences in perspectives and economic problems. To solve problems that occur in marriages of different ages, the following methods are used by informants to solve problems in the household, namely: discussing and ignoring each other. There are several things that couples with different ages do in building household harmony including being honest, being open to each other, trusting each other and staying closer to Allah SWT.